Genomic Characterization of MDR Escherichia coli Harboring blaOXA-48 on the IncL/M-type Plasmid Isolated from Blood Stream Infection. (28th June 2018) - Alousi, S.; Salloum, T.; Arabaghian, H.; Matar, G. M.; Araj, G. F.; Tokajian, S. T.
Abstract : Escherichia coli is responsible for a wide variety of community and hospital acquired extraintestinal infections, and the emergence of ESBL resistant isolates is a major clinical concern. In this study, we characterized the genomic attributes of an OXA-48 and CTX-M-3 producing E. coli EC-IMP153. Whole-genome initial assembly produced 146 contigs with a combined 5, 504, 170 bp in size and a G+C content of 50.5%. wgSNPs-based phylogenetic comparison with 36 publically available genomes was also performed. Comprehensive genomic analysis showed that EC-IMP153 belonged to sequence type ST-405 and harbored several resistance determinants including the β -lactam resistance genesb l a O X A - 48, b l a C T X - M - 3, b l a T E M - 1 B, b l a OXA-1, andb l a CMY-70, aminoglycoside fyuA and aac(3)IId, tetracycline tet(A) and tet(R), and fluoroquinolone gyrA, parC, and mfd resistance determinants . Plasmids with the following incompatibility groups were detected in silico and confirmed using PBRT: IncI1-α, IncL, IncW, Col (BS512), and IncF. To our knowledge this is the first in-depth genomic analysis of an OXA-48 producing E. coli ST-405 isolated from a patient in Lebanon and linked to a blood stream infection. Continuous monitoring is necessary to better understand the continued diffusion of such pathogens, especially in view of the population movements triggered by unrest in the Middle East.